Les mines de fer de Schefferville - Journaux, André; Taillefer, François (Cahiers de géographie du Québec, 1957)
The iron mines of Schefferville, at a latitude of 55° N., are the first mines exploited in one of the best provided iron ore regions in the World ; the geosynclinal of Labrador. Their distance from the sea (360 miles to the estuary of the St. Lawrence) is compensated for by the richness of the ore deposits : abundant reserves, high percentage yield, and the quality of the mineral.The ore is mined in open pits ; the main difficulty is the harshness of the climate, which necessitates the interruption of operations from the end of November to the middle of April. The deposits are found in a subarctic taiga zone. It has been necessary to bring in all the workers ; mostly French Canadians, but also some foreigners. All tools and provisions have to be transported a great distance. The ore production is increasing rapidly : 2.25 million tons in 1954, 6 million tons in 1955, and 12 million tons in 1956. It will reach 20 million tons within the next few years. The ore is transported entirely by the railroad specially built to the port of Sept-Iles, from which it reaches, either by the sea route or by the St. Lawrence, the iron-smelting region of the north-eastern United States, where the principal outlets of the Iron Ore Co. of Canada are found. The port of Sept-Iles, which had a population of 5,573 in 1956, compared to that of 1,866 in 1951, could very possibly see its importance increase when the completion of the St. Lawrence Seaway will allow prairies grain, and possibly Pennsylvania coal, to serve as return freight for the iron ore. Close to the mines, Schefferville already has 3,500 inhabitants and has become the largest town in Labrador. Besides its purely mining junctions there are others, in particular that of a supply centre and of a transportation terminus. Its population is becoming progressively more stable and of a more balanced composition. The camp of the first prospectors is thus transformed into a permanently populated centre, of which the legal existence was recognized on the first of August, 1955.